Robust Exploration Strategies for a Robot exploring a Wireless Network - Blum, Christian; Hafner, Verena (Electronic Communications of the EASST, 2013)
Integration of robots into wireless networks is important for a number of scenarios. One of the tasks is network exploration for which the most basic case is finding the physical outline of the network. We propose a robust algorithm for exploring the outline of a network with a mobile robot. For this algorithm we study robustness against noise for several sensory inputs.